Correlation of Renal Function Tests with Ultrasonographic Findings in Chronic Kidney Disease - Phuntanasiri, Supharat (Journal of The Department of Medical Services, 2021)
Background : Prediction of renal function based on ultrasonographic findings could be very useful for evaluation and management of chronic kidney disease (CKD) patients. Objective : The purpose of this study was to evaluate the correlation between renal function tests (serum creatinine and estimated glomerular filtration rate [eGFR]) and renal ultrasonographic findings (anterior-posterior diameter [AP], transverse diameter [TD], renal length [RL], parenchymal thickness [PT] and parenchymal echogenicity [PE]) in CKD patients. Method : A retrospective study of the above ultrasonographic parameters and renal function tests in CKD patients with stage 2-5 was analyzed for their correlation using correlation coefficient and multiple linear regression analyses. Result : A total of 237 patients (mean age of 70 years) were eligible in this study; 147 of them had CKD associated with hypertension and diabetes mellitus (HTDM) while the remaining cases were associated with hypertension only (HT). Both HT-DM and HT groups had similar levels of serum creatinine (3.02 ± 2.30 vs. 2.85 ± 2.65 /dl) but significantly different eGFR (24.0 ± 11.7 vs. 29.3 ± 14.5 ml/min/1.73 m2, p=0.004). Serum creatinine and eGFR were found to correlate with renal ultrasonographic parameters differentially depending on the CKD causes. For serum creatinine, it showed positive correlations with AP, TD, RL and PT in the HT-DM patients, having Spearman’s correlation coefficients (r) of 0.31, 0.32, 0.22 and 0.30, respectively, while it correlated negatively with AP (r=-0.25) and positively with PE (r=0.51) in the HT patients. For eGFR, it negatively correlated with only PE (r=-0.23) in the HT-DM group but showed significant correlations with AP, TD, PT and PE (r=0.40, 0.35, 0.24 and -0.57) in the HT group. To evaluate the effects of the renal ultrasonographic parameters on eGFR prediction, multiple linear regression analysis was performed. In the HT-DM group, PE was the only significant factor effecting eGFR prediction, whereas AP, RL, PT and PE were the significant factors in the HT group. Moreover, the prediction model of the HT patients showed a higher correlation with actual eGFR compared with that of the HT-DM patients; the coefficients of multiple correlation were 0.727 and 0.388, respectively. Conclusion : The renal function tests based on serum creatinine and eGFR showed significant correlations with renal ultrasonographic findings differentially depending on the CKD etiology. The renal parameters of the HT group demonstrated a higher correlation with eGFR, which is widely used for CKD staging, compared with the HT-DM group. Thus, they could potentially be useful for evaluation of the kidney function in addition to the use of eGFR, particularly in the CKD patients with hypertension.